Pengaruh Harga, Inovasi, dan Kualitas Produk Terhadap Kepuasan Konsumen Di RM Cak Sur Sigura Gura Malang - Joni Iskandar; Nur Hidayati; Arini Fitria Mustapita (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstackThe purpose of this study was to determine the Effect of Price, Innovation, and Product Quality on Consumer Satisfaction at RM Cak Sur Sigura - Gura Malang. The variables used are price, innovation, and product quality as independent variables. Whereas Consumer Satisfaction is the dependent variable. The population in the study were 150 consumers. The sampling method in this study was purposive sampling with a total sample of 60 respondents. Quantitative methods with multiple linear regression analysis techniques. Based on the results of this study it can be concluded as follows: (a) Price, Innovation, and Product Quality simultaneously affect customer satisfaction at RM Cak Sur Sigura - Gura Malang. (b) Price influences customer satisfaction at RM Cak Sur Sigura - Gura Malang. (c) Innovation influences consumer satisfaction at RM Cak Sur Sigura - Gura Malang. (d) Product quality influences consumer satisfaction at RM Cak Sur Sigura - Gura Malang.Keyword :Price, Innovation, Consumer satisfaction, Product quality